Hybrid solar cells based on Si and PEDOT : PSS - Wang, Hao (2016)
As the demand for renewable clean energy increases, extensive research has been directed towards photovoltaics (PV) energy owing to its inexhaustibility, abundance and availability anywhere on earth. Although the conventional crystalline bulk silicon (Si) solar cells which dominate the current commercial PV markets are highly efficient and reliable, the costly Si material and fabrication processes make them not as competitive as fossil fuels. To lower the cost, hybrid solar cells based on Si and organic materials have emerged as promising candidates to leverage on the advantages of the highly efficient Si material and the low cost and flexibility offered by organic materials. Si nanostructures have also drawn much attention and been widely incorporated into the hybrid cells due to their excellent capabilities in light trapping and carrier separation and collection. In this work, we fabricate and characterize different types of high efficient Si/PEDOT:PSS hybrid solar cells, that include planar cells and cells incorporated with Si nanowires (SiNWs) and Si nanocones (SiNCs). These cells were fabricated on both bulk Si wafers as well as Si thin films. The study of such hybrid cells using Si thin films is important to lower the material cost and render them suitable for practical application. Besides experimental studies, extensive theoretical simulation has been carried out to understand the optical characteristics and light trapping of the nanostructures. Firstly, we study the performance of simple planar Si/PEDOT:PSS hybrid cells, focusing on the thickness of the PEDOT:PSS coating and the Si absorber layer on the light absorption behavior. Simple planar hybrid heterojunction solar cells have been fabricated based on n-type Si and the p-type PEDOT:PSS polymer using a simple low-temperature spin-coating technique. Cells with different thicknesses of PEDOT:PSS layer have been fabricated to study the effect of the polymer thickness on the cell performance. It is found that an optimum PEDOT:PSS thickness of ~78 nm gives rise to the highest short circuit current density (Jsc) and external quantum efficiency (EQE) of 27.0 mA/cm2 and 63.6%, respectively. Hybrid cells with different thicknesses of Si thin films from 2.2 to 15.5 µm have also been fabricated to study their photovoltaic performance. It is found that a high power conversion efficiency (PCE) of 8.7% has been achieved for the cell with the thickest Si film thickness of 15.5 µm. It exhibits a Jsc of 20.4 mA/cm2, which is about 78% of that measured for a reference bulk wafer Si cell fabricated in the same process. Concurrently, we have performed optical simulations for the planar hybrid cell structure based on the finite element method. The effects of both the PEDOT:PSS thickness and the Si thickness on the light harvesting characteristics are investigated and compared with the experimental results. It is found that a high photocurrent density of ~ 24 mA/cm2 is achievable for a hybrid cell based on 10 µm Si film using layer of PEDOT:PSS with an optimum thickness of 80~90 nm. Taken into account a larger resistance when a thicker PEDOT:PSS is used, our experimental and simulation results suggest that the optimum PEDOT:PSS thickness for thin film hybrid cells is around 70~80 nm. With only a layer of 15 µm thick Si film, the planar hybrid cell based on the backPEDOT structure is able to achieve a high photocurrent density of 30.3 mA/cm2 and a PCE of 13.2%. Next we study the light harvesting capability and photovoltaic performance of Si/PEDOT:PSS hybrid cells incorporated with SiNWs arrays fabricated using the metal-catalyzed electroless etching (MCEE) technique. The surfaces of the SiNWs prepared using this technique are typically defective and contaminated with Ag nanoparticles, which will lead to enhanced carriers recombination and adversely affect the performance of the cells. In this work, a simple two-step surface treatment method using ozone has been proposed to improve the surface quality of SiNWs in SiNWs/PEDOT:PSS hybrid cells. A remarkable PCE of 12.4% has been achieved, with a high Jsc of 30.8 mA/cm2 and a high Voc of 0.58 V. This is due to the enhancement of light absorption attributed to the light trapping by the SiNWs, and suppression of recombination loss arising from the removal of Ag nanoparticles and passivation of the SiNWs surface brought about by the proposed two-step surface treatment process. The PCE and Voc are 29.8% and 13.7% enhanced respectively as compared to similar SiNWs hybrid cells without the surface treatment. Besides using bulk Si wafers, SiNWs/PEDOT:PSS based on the more cost-effective Si thin films have also been studied. The same two-step surface treatment process, using oxygen (O2) plasma instead of ozone, has been applied to the thin film SiNWs/PEDOT:PSS cells to remove contaminants and passivate the SiNWs surface. The performance of the thin film SiNWs/PEDOT:PSS hybrid cells have been investigated in terms of the effects of the surface treatment and the SiNWs length. It is found that similar improvements in the SiNWs surface quality can also be achieved with the use of oxygen plasma treatment. In terms of cell performance, a maximum PCE of 7.83% has been obtained for a Si thin film of 10.6 µm thick under the optimized SiNWs length of 0.7 µm.